Gender, Emotional Intelligence and Conflict Resolution Proficiency of Managers in Nigerian Organizations - Mwantu, Esau Nanfwang; Jampak, Alex; Dastu, Richard Ringle; Ibanga, Monica; Shitery, Irmiya Bhandi; Agun, Lami Ayuba (NIU Journal of Humanities; Vol 2 No 2 (A) (2017): KIU Journal of Humanities, Vol. 2 No. 2 (A), December 2017, 2018)
This study investigated the influences of gender and emotional intelligence on managers’ conflict resolution proficiency in public and private organizations in Jos, Nigeria using one hundred participants (52 males and 48 females). Findings of the study revealed a significant effect of emotional intelligence on managers’ conflict resolution proficiency (t (1, 99) = -18.364, P<0.05). Results also showed that significant differences exist between female and male managers’ conflict resolution proficiency t (1, 99) = -72.859, p<0.05. The study further revealed an interactive influence of the two variables on managers’ conflict resolution proficiency F (1, 99) = -13.462, P<0.05. Based on findings of the study, we recommend that organizations should adopt the policy of recruiting male and female managers with high EI and high conflict management proficiency. This is because hiring employees and managers who have these characteristic traits yields twice as much result compared to those with low EI and low conflict management proficiency. Organizations should also provide conflict management proficiency training to their managers for efficient and effective performance. Lastly, changes should be effected in the design of today’s organizations to accommodate flatter, decentralized, and less complex social systems that will make it easier for the managers to manage in order to reduce conflict in the organization to its barest minimum.